2013
DOI: 10.5455/bcp.20130421014758
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Patients with Coronary Artery Disease

Abstract: Koroner arter hastalığı olan hastalarda anksiyete ve depresyon Amaç: Önceki prospektif çalışmalarda depresyonun miyokardiyal enfarktüs ve kardiyovasküler mortalite için bağımsız bir risk faktörü olduğu bildirilmiştir. Anksiyete bozukluklarının da koroner arter hastalığı (KAH) ile ilişkili olduğu bilinmektedir. Psikolojik faktörler de sigara içme, azalmış fiziksel aktivite, kötü diyet ve tedaviye uyumun azalması gibi davranışsal mekanizmalar ile KAH seyrini etkileyebilmektedir. Bu çalışmanın amacı KAH şüphesiyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
(31 reference statements)
0
9
0
4
Order By: Relevance
“…The consumption of products containing SC may lead to serious adverse effects [ 3 ]. Previous studies show that psychiatric disorders may also lead to an increased risk of cardiovascular disease (CVD) [ 4 , 5 , 6 ]. There is a bidirectional relationship between CVD and depressive disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of products containing SC may lead to serious adverse effects [ 3 ]. Previous studies show that psychiatric disorders may also lead to an increased risk of cardiovascular disease (CVD) [ 4 , 5 , 6 ]. There is a bidirectional relationship between CVD and depressive disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, demonstrated that preoperative assessment of depressive symptoms in addition to the evaluation of biomedical risk factors is essential to anticipate which patients are likely to show the poor health‐related quality of life after cardiac surgery . A study of 116 patients who underwent coronary angiography showed that patients with abnormal coronary angiography had a higher prevalence of anxiety and depression than normal . In addition to the effects of psychological factors, behavioral factors such as increased rate of smoking, impaired dietary habits, increased consumption of alcohol and substance use, and nonadherence to treatment also have an effect on the development of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…In the study to determine the effect of informing patients about diagnosis procedures on their anxiety, Ertin et al (1999) 22 found that 69% of the patients had anxiety out of being unaware of what the result of the procedure would be and 14% of them concerned with the process because it may be painful. Sunbul et al (2013) 23 assessed in their study the level of anxiety in patients who underwent a CAG and they found that the patients whose CAG result was normal had a mean state anxiety score of 40.4 ± 4.3 and the patients who had ≥50% atherosclerotic stenosis or had a slow coronary flow had a mean score of 45.3 ± 5.5. Vural et al…”
Section: Discussionmentioning
confidence: 99%